Nitric oxide synthesis in patients with infective gastroenteritis. Issue 3 (1st September 1999) - Forte, P; Dykhuizen, R S; Milne, E; McKenzie, A; Smith, C C; Benjamin, N
Abstract : BACKGROUND: There is evidence that endogenous nitrate synthesis is notably increased in patients with infective gastroenteritis. AIMS: To determine whether this is due to nitric oxide (NO) production via the l -arginine/NO pathway. METHODS: Seven male patients with community acquired bacterial gastroenteritis and 15 healthy male volunteers participated in this study. All patients had stool culture positive infective gastroenteritis. A bolus of 200 mgl -[ 15 N]2 -arginine was administered intravenously after an overnight fast. Urine was collected for the next 36 hours. Urinary [ 15 N: 14 N]nitrate ratio was assessed by dry combustion in an isotope ratio mass spectrometer. RESULTS: Mean 36 hour total urinary nitrate excretion in the gastroenteritis group was 5157 (577) μmol compared with 2594 (234) μmol in the control group (p<0.001). Thirty six hour urinary [ 15 N]nitrate excretion was considerably higher in the gastroenteritis group compared with the control group (13782 (1665) versus 1698 (98) ηmol; p<0.001). These values represent 1.129 (0.139)% and 0.138 (0.007)% of [ 15 N]nitrogen administered (p<0.001), respectively. Corrected 36 hour urinary [ 15 N]nitrate excretion for urinary creatinine was also significantly higher in the patient compared with the control group (1934 (221) versus 303 (35) ηmol/mmol; p<0.001). CONCLUSION: Results show notably enhanced nitrate synthesis due to increased activity of thel -arginine/NO pathway in patients with infective gastroenteritis.